2018
DOI: 10.1073/pnas.1719065115
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency AFM reveals lipid membrane mechanical properties and the effect of cholesterol in modulating viscoelasticity

Abstract: The physical properties of lipid bilayers comprising the cell membrane occupy the current spotlight of membrane biology. Their traditional representation as a passive 2D fluid has gradually been abandoned in favor of a more complex picture: an anisotropic time-dependent viscoelastic biphasic material, capable of transmitting or attenuating mechanical forces that regulate biological processes. In establishing new models, quantitative experiments are necessary when attempting to develop suitable techniques for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 64 publications
(85 reference statements)
3
54
0
Order By: Relevance
“…Regions with a low concentration of cholesterol molecules are predominantly elastic while regions with a high concentration have viscoelastic properties. 249 High-spatial resolution nanomechanical maps characterized the adsorption of single alkali cations on lipid bilayers. 250 It was reported that the formation of an ionic network reduces the elastic modulus of the lipid bilayer.…”
Section: Bimodal Afmmentioning
confidence: 99%
“…Regions with a low concentration of cholesterol molecules are predominantly elastic while regions with a high concentration have viscoelastic properties. 249 High-spatial resolution nanomechanical maps characterized the adsorption of single alkali cations on lipid bilayers. 250 It was reported that the formation of an ionic network reduces the elastic modulus of the lipid bilayer.…”
Section: Bimodal Afmmentioning
confidence: 99%
“…1,6,8,[16][17][18][19][20][21] Bimodal AFM provides a very fast, high resolution and accurate method to map the elastic properties of polymers and biomolecules. 22,23 It has been applied to determine with very high spatial resolution the elastic modulus of a large variety of materials and macromolecules such as antibodies 24 and other proteins, [25][26][27] DNA, 28,29 cells, 30,31 bone microconstituents, 32 lipid bilayers, 33,34 self-assembled monolayers, 35,36 2D materials 37 or organic semiconductor devices. 38 This technique can be operated in air or liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The exhaustive list of AFM imaging modes is very long. Many of the recently developed modes are used for studying a number of biological samples, including proteins; small biological fibrils, like lipid membranes; amyloid fibrils; and viruses with the microcantilever as the sensing element [ 121 , 122 ]. Moreover, it has been demonstrated that malign and benign cell lines present significant differences in their viscoelastic response using MMM [ 123 ].…”
Section: Modes Of Operations Of Cantilever-based Afmmentioning
confidence: 99%